Molecular characterization of ultrafine particles using extractive electrospray time-of-flight mass spectrometry. Issue 6 (23rd August 2021) - Surdu, Mihnea; Pospisilova, Veronika; Xiao, Mao; Wang, Mingyi; Mentler, Bernhard; Simon, Mario; Stolzenburg, Dominik; Hoyle, Christopher R.; Bell, David M.; Lee, Chuan Ping; Lamkaddam, Houssni; Lopez-Hilfiker, Felipe; et al.
Abstract : Using real-time simultaneous gas- and particle-phase data, the condensation of naphthalene and β-caryophyllene oxidation products on a molecular level is discussed. Abstract : Aerosol particles negatively affect human health while also having climatic relevance due to, for example, their ability to act as cloud condensation nuclei. Ultrafine particles (diameter D p < 100 nm) typically comprise the largest fraction of the total number concentration, however, their chemical characterization is difficult because of their low mass. Using an extractive electrospray time-of-flight mass spectrometer (EESI-TOF), we characterize the molecular composition of freshly nucleated particles from naphthalene and β-caryophyllene oxidation products at the CLOUD chamber at CERN. We perform a detailed intercomparison of the organic aerosol chemical composition measured by the EESI-TOF and an iodide adduct chemical ionization mass spectrometer equipped with a filter inlet for gases and aerosols (FIGAERO-I-CIMS). We also use an aerosol growth model based on the condensation of organic vapors to show that the chemical composition measured by the EESI-TOF is consistent with the expected condensed oxidation products. This agreement could be further improved by constraining the EESI-TOF compound-specific sensitivity or considering condensed-phase processes. Our results show that the EESI-TOF can obtain the chemical composition of particles as small as 20 nm in diameter with mass loadings as low as hundreds of ng m −3 in real time. This was until now difficult to achieve, as other online instruments are often limited by size cutoffs, ionization/thermal fragmentation and/or semi-continuous sampling. Using real-time simultaneous gas- and particle-phase data, we discuss the condensation of naphthalene oxidation products on a molecular level.